Patient safety in a rural sub-Saharan Africa hospital: A 7-year experience at the AIC Kijabe Hospital, Kenya. - Peter M Nthumba; Caroline Mwangi; Moses Odhiambo (Public Library of Science (PLoS), 2024)
The development of a safety culture is challenging, primarily because it often disrupts institutional attitudes, norms and values. In the healthcare industry, most of the data on the results of unsafe care come from High-Income Countries. The Hospital Survey on Patient Safety Culture (HSOPS) is a tool for assessing, building, sustaining and comparing institutional safety cultures within healthcare organizations. We used the HSOPS over a 7-year period, and herein report our experience. The authors report their experience using the HSOPS tool in Kijabe Hospital, an institution with 650 employees, over a 7-year period. The HSOPS tool, with no local modifications, was distributed to all employees during each survey. The institutional HSOPS percent positive dimension scores for 2015, 2017 and 2019 were compared with baseline data from the 2013 survey. The average response rate during the study period was 84.5% (range 65.1% to 93.6%). In general, the mean percentage positive dimension scores of most domains improved in the 2019 survey (p<0.05), including reduced staff turnover and, improved hospital support for patient safety (p<0.0001), amongst other domains. The overall patient safety grade (excellent/very good), was 50% (range 43-64%). Although the dynamics of high staff turnover and hospital leadership change presented challenges in developing and measuring institutional patient safety culture, this study demonstrates that patient safety ideals can be developed and embraced in sub-Saharan Africa. Patient safety champions, a generative institutional leadership that is supportive of patient safety, are important for the development of an institutional safety culture. Creating an institutional just culture creates a patient safety culture.